2015
DOI: 10.1371/journal.pone.0128708
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2-Receptor Antagonists Down-Regulate CYP1A1/2 and CYP1B1 in the Rat Liver

Abstract: Dopaminergic systems regulate the release of several hormones including growth hormone (GH), thyroid hormones, insulin, glucocorticoids and prolactin (PRL) that play significant roles in the regulation of various Cytochrome P450 (CYP) enzymes. The present study investigated the role of dopamine D2-receptor-linked pathways in the regulation of CYP1A1, CYP1A2 and CYP1B1 that belong to a battery of genes controlled by the Aryl Hydrocarbon Receptor (AhR) and play a crucial role in the metabolism and toxicity of nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 69 publications
3
19
0
Order By: Relevance
“…It is found that the antagonists of D2 dopaminergic receptors interfere with the regulation if CYP2C enzymes. 85,86 This can support the link between interfering dopamine transportation and CYP2C19 activity highlighted in the rules. Secondly is the combination of CD40 with IL-8 cytokine.…”
Section:  Combined Bioactivity Readoutsmentioning
confidence: 65%
“…It is found that the antagonists of D2 dopaminergic receptors interfere with the regulation if CYP2C enzymes. 85,86 This can support the link between interfering dopamine transportation and CYP2C19 activity highlighted in the rules. Secondly is the combination of CD40 with IL-8 cytokine.…”
Section:  Combined Bioactivity Readoutsmentioning
confidence: 65%
“…Dopaminergic systems regulate the release of several hormones, including growth hormone (GH), thyroid hormones, insulin, glucocorticoids, and prolactin (PRL), which play significant roles in the regulation of various CYP450 enzymes. Inhibition of dopamine D2-receptors with sulpiride (SULP) significantly repressed the constitutive and benzo[a]pyrene (B[a]P)-induced cyp1a1, cyp1a2, and cyp1b expression in the rat liver, which appears to be mediated by activation of the insulin/PI3K/AKT pathway [38]. Injection of 5,7-DHT decreased serotonin concentration in the brain, followed by a significant rise in the levels of growth hormone, corticosterone, and testosterone, and a drop in triiodothyronine concentration in the serum.…”
Section: Discussionmentioning
confidence: 99%
“…CGS21680 has been shown to also bind to adenosine A 1 receptors at a 140-fold higher concentration than for A 2A receptors . Information regarding the hepatic metabolism of these compounds has not be reported, though L-741,626 significantly inhibits the gene expression of many cytochrome P450 enzymes including CYP1A1, CYP1A2, CYP1B1, CYP2C11, CYP2D1, CYP2D2, CYP2E1, CYP3A1, and CYP3A2 (Daskalopoulos et al, 2012;Harkitis et al, 2015).…”
Section: Pharmacological Reduction Of Repetitive Behaviorsmentioning
confidence: 99%